Analisis Perkuatan Stabilitas Struktur Dinding Penahan Tanah (Sheet Pile) Dermaga yang Tidak Sesuai Detail Engineering Design (DED) - Irawan, Farid; Agus Sulaeman; Xbal Meiprasetyo (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2025)
A wharf is a key infrastructure at a port that functions as a place for ships to dock and moor while conducting the loading and unloading of cargo, as well as passenger activities. The structural integrity of the wharf, especially along the bank, must be carefully designed to ensure ships can anchor securely. In pier construction, slope reinforcement is often done using sheet piles. When designing sheet piles, important factors such as pile depth and soil type must be considered. However, in practice, challenges arise when the construction in the field does not align with the specifications outlined in the Detail Engineering Design (DED), potentially compromising the wharf’s stability. This research aims to determine whether the reinforcement already implemented meets safety standards and technical requirements to prevent structural failure. A civil engineering approach is applied by reanalyzing the stability of existing reinforcements. The method involves evaluating the strength of the pier structure using various reinforcement types, including Corrugated Concrete Sheet Pile (CCSP), Concrete Sheet Pile (CSP), and Tie Rods. These evaluations are carried out through numerical calculations and structural analysis using the Plaxis program to simulate performance and ensure the design's reliability under both normal and seismic conditions.